THE USE OF RUQYAH QUR’ANIYAH THERAPY ON THE EFFECT OF BRAIN WAVES HEALING TOURETTE SYNDROME PATIENTS - Muhamad Ali Mustofa Kamal; Norita Md Norwawi; Nor Azila Noh; Robiatul Adawiyah Mohd (Analisa: Journal of Social Science and Religion, 2022)
Ruqyah is a prayer therapy used for specific treatments, which consists of a particular series of readings from the sources of the verses of the Qur’an and the hadith of the Prophet Muhamad SAW. Imam Qurtubi believed that ‘ruqyah quraniyah’ therapy could contribute to healing physical and spiritual ailments. The resonance effect on the ruqyah therapy of the verses of the Qur’an has a tremendous impact on each reading that is heard (voiced) for various objects. The Research question in this research is how the effectiveness of using ruqyah quraniyah on the effect of brain waves on the healing of Tourette syndrome patients at dr.Sardjito Yogyakarta? This study uses a qualitative method with an experimental phenomenological approach. The experimental stage stimulated it with a variant of the codification of the ruqyah verses in the form of ‘Hizb Bahr,’ which was tested on pediatric neurology patients for eight weeks so that the patient’s brain memory records resulted in refraction and habits. This result indicates that patients with TS change to improve along with psychological conditions that can be calmed by listening to the beauty of the ‘Hizb Bahr’ in daily life for eight consecutive weeks. The state of listening to the beauty of reading the Qur’an in this ‘ruqyah quraniyah’ codification model essentially conditions the patient’s brain waves at the alpha level. No frontal beta makes the patient perform reflex activities as long as his psychological state is calm and controlled.